2020
DOI: 10.46717/igj.54.1a.3ms-2021-01-24
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Industrial Ceramic (Cordierite) from Iraqi Raw Materials Through Solid-State Sintering Method

Abstract: This study uses Iraqi raw materials (Western Desert) which include: Urdhuma silica sand, Duekhla kaolinitic claystone, flint clay, porcelanite, and karst bauxite, alongside other materials (pure silica created as by-product of Qaim phosphate manufacturing processes.), amorphous silica (silica from rice husk ash), Mg (OH)2, and MgCO3. The raw materials have been crushed and milled into sizes smaller than 45µ except the silica sand and kaolin that have been miled into different sizes 20 and 45 µ. Twenty-seven mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…and Awadh and Awad (2021) manufactured perforated and ordinary bricks using injana claystone in Karbala-Najaf plateau in the middle of Iraq, the researchers concluded that Injana claystone is suitable for such purposes. Najim and Yousif (2021) studied the Synthesis of Industrial Ceramic (Cordierite) from Iraqi Raw Materials Through Solid-State Sintering Method in Western Dessert used XRD for measuring the best mixture for preparing cordierite ceramics. The main objectives of this study are to find out the validity of the Injana, Mukdadiyah, and Bai Hassan formations, with Quaternary deposits for the ceramic industries, through the evaluation of the potential uses of their clays in some ceramic industries using mineralogical, chemical, and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…and Awadh and Awad (2021) manufactured perforated and ordinary bricks using injana claystone in Karbala-Najaf plateau in the middle of Iraq, the researchers concluded that Injana claystone is suitable for such purposes. Najim and Yousif (2021) studied the Synthesis of Industrial Ceramic (Cordierite) from Iraqi Raw Materials Through Solid-State Sintering Method in Western Dessert used XRD for measuring the best mixture for preparing cordierite ceramics. The main objectives of this study are to find out the validity of the Injana, Mukdadiyah, and Bai Hassan formations, with Quaternary deposits for the ceramic industries, through the evaluation of the potential uses of their clays in some ceramic industries using mineralogical, chemical, and physical properties.…”
Section: Introductionmentioning
confidence: 99%